The influence of alumina ratio on the properties of the Al-MCM-41 mesoporous structure - غندور أيهم; ابراهيم راهب; حسام الركاد (Latakia University Journal -Basic Sciences Series, 2024)
Three samples of the mesoporous structure Al-MCM-41 were prepared by hydrothermal treatment method using silica and a structure-oriented agent (CTRB), with a molar ratio of Silica:CTAB is 1: 0.5 with a chang in the aluminum ratio so that it was (0-10-20)% . The results showed that the changing of alumina ratio was affected notely on the prepared structures. Whereas, the specific surface area was decreased from 874.0 to 329.7 and 88.9 m2/g when the alumina ratio 0,10,and 20% respectively, and the total pore volume decreased from 0.63 to 0.35 and 0.24 ml/g according to alumina ratio 0,10,and 20% respectively. The pore radius increased from 14.4 to 21.5 and 53.7 ºA for alumina ratio 0,10,and 20%, while . The pore volume distribution was decreased from 28 for alumina ratio 0% to 12% for both alumina ratio 10 and 20%. While a convergence was observed in the spectra of XRD diffraction, and infrared spectra (FT-IR) with a slight difference as the shift of the peak or disappearance of the other with the increase in the molar ratio of aluminum..